Nutritional concerns in pediatric inflammatory bowel disease - Yong Joo Kim (Korean Pediatric Society, 2016)
The pathophysiology and fundamental etiologic mechanism of inflammatory bowel disease (IBD) is not well understood even though therapeutic regimens and drugs are rapidly evolutionary. IBD has complicated connections with genetic, immunologic, gut microbial, environmental, and nutritional factors. It is not clearly well known to the physicians how to feed, what nutrients are more helpful, and what food to be avoided. This review discusses the issues of growth and important nutritional concerns in the management of IBD in childhood.